Coral geochemical response to uplift in the aftermath of the 2005 Nias–Simeulue earthquake - Sindia M. Sosdian; Michael K. Gagan; Danny H. Natawidjaja; Alena K. Kimbrough; Bambang W. Suwargadi; Hamdi Rifai; Heather Scott-Gagan; Dudi Prayudi; Imam Suprihanto; Wahyoe S. Hantoro (Scientific Reports, 2024)
Abstract On 28 March 2005, the Indonesian islands of Nias and Simeulue experienced a powerful Mw 8.6 earthquake and coseismic uplift and subsidence. In areas of coastal uplift (up to ~ 2.8 m), fringing reef coral communities were killed by exposure, while deeper corals that survived were subjected to habitats with altered runoff, sediment and nutrient regimes. Here we present time-series (2000–2009) of Mn/Ca, Y/Ca and Ba/Ca variability in massive Porites corals from Nias to assess the environmental impact of a wide range of vertical displacement (+ 2.5 m to − 0.4 m). High-resolution LA-ICP-MS measurements show that skeletal Mn/Ca increased at uplifted sites, regardless of reef type, indicating a post-earthquake increase in suspended sediment delivery. Transient and/or long-term increases in skeletal Y/Ca at all uplift sites support the idea of increased sediment delivery. Coral Mn/Ca and Ba/Ca in lagoonal environments highlight the additional influences of reef bathymetry, wind-driven sediment resuspension, and phytoplankton blooms on coral geochemistry. Together, the results show that the Nias reefs adapted to fundamentally altered hydrographic conditions. We show how centuries of repeated subsidence and uplift during great-earthquake cycles along the Sunda megathrust may have shaped the modern-day predominance of massive scleractinian corals on the West Sumatran reefs.